The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.4103/0019-5545.39760
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-like activity of tramadol in mice

Abstract: Objective:To evaluate antidepressant-like effect of tramadol in mice.Materials and Methods:Tramadol was administered at three different doses (10, 20, and 40 mg/kg, i.p.) once daily for 7 days to Swiss albino mice of either sex. The immobility period of control and drug-treated mice was recorded in forced swim test (FST). The antidepressant effect of tramadol was compared to that of fluoxetine (20 mg/kg, i.p.), administered for seven successive days.Results:Tramadol produced significant antidepressant effect a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 11 publications
2
23
1
Order By: Relevance
“…in low doses as well as in high doses. 15 But in the present study we found that tramadol was not that much effective in low doses as it was in high doses. They also compared the efficacy of tramadol with fluoxetine like previous study, but we compared the efficacy of tramadol with imipramine.…”
Section: Discussioncontrasting
confidence: 75%
“…in low doses as well as in high doses. 15 But in the present study we found that tramadol was not that much effective in low doses as it was in high doses. They also compared the efficacy of tramadol with fluoxetine like previous study, but we compared the efficacy of tramadol with imipramine.…”
Section: Discussioncontrasting
confidence: 75%
“…However at higher dosage of 40mg/kg, significant antidepressant activity was seen compared to imipramine. Our finding was concurred by studies of Rojas et al, Kumar A et al and Karla B et al [14][15][16] which evaluated Tramadol using FST model. Tramadol at higher dose inhibits more number of transporters which results in increased reuptake inhibition.…”
supporting
confidence: 92%
“…On 14 th day the test was performed 30 mins after administration of drugs same as that of single dose study. 8 Open field test [7][8][9][10] This test utilizes behavioral changes in rodents exposed to novel environment and is used to confirm that the observed antidepressant effect is not due to stimulation of general motor activity. Open field apparatus have been used to test the mice.…”
Section: Methodsmentioning
confidence: 99%